Examining the influences on the use of behavioural science within UK local authority public health: Qualitative thematic analysis and deductive mapping to the COM-B model and Theoretical Domains Framework - Moffat, Abby; Cook, Erica Jane; Chater, Angel Marie (Frontiers in Public Health, 2022)
Background Behavioural science and its contribution towards improving public health is receiving increased recognition. Yet, the translation of these insights into public health practice is under-researched. This study explored the factors influencing the use of behavioural science within public health at a local authority level. Methods Fourteen local authority staff (n = 13 female) in the south of England participated in semi-structured interviews, which were analysed inductively to identify key themes. These were later mapped deductively to the COM-B model and Theoretical Domains Framework. Findings Nine themes were identified as factors that influence the use of behavioural science in local authority public health: (1) “Limited past experience,” (2) “Narrow understanding,” (3) “Perceived value of behavioural science,” (4) “Translational gap from theory-to-practice,” (5) “No protected time,” (6) “Old ways of working,” (7) “Political influence and organisational culture,” (8) “Relationships with key stakeholders,” (9) “Access to behavioural science resources”. Deductive mapping of these themes revealed that five of the COM constructs (excluding Physical Capability) and eleven of the TDF domains influenced behavioural science use, with “Social influences” and “Knowledge” being the most prominent. Discussion Use of behavioural science within local authority public health practice is limited and inconsistent. For it to be successfully implemented, there must be an understanding of its role and value, alongside strategies to overcome a translational gap from theory to practice. Public health teams would benefit from protected time to enable application and strategies to break old habits of using a common-sense approach. System-wide buy-in, particularly related to senior leadership and system partners is needed, which would benefit from organisational and political culture change. Training opportunities, practical resources and expert in-house support should be considered a priority across public health teams.